UPAYA MENINGKATKAN KETERAMPILAN MENCERITAKAN HASIL PENGAMATAN/KUNJUNGAN MENGGUNAKAN METODE SOSIODRAMA KELAS V MI MA’ARIF BLONGKENG - Ditya Riani Lasdriana; C. Indah Nartani (Universitas Sarjanawiyata Tamansiswa, 2015)
Abstract: The purpose of this study was to determine the improvement of the students’ skills in telling observations/visits among the fifth grade students of MI Ma'arif Blongkeng by sociodrama. The type of this study was a classroom action research. Data collection techniques used observation and field notes. The research instrument used observation sheets and sheets assessment of telling observation/ visit. Data analysis used quantitative data by finding the mean and percentage. Based on the results of research and discussion that has been conducted in MI Ma'arif Blongkeng can be concluded that the value of students has increased both from pre cycle to cycle I and cycle II. Based on the results of the analysis showed that the average percentage of student activity on pratindakan every aspect of 57.1% with good qualifications. The increasement in the first cycle was 73.8%. In the second cycle increased 86.9% with excellent qualifications. In general, based on observation of student activity guidelines has increased very significantly after the applied methods sociodrama. Skills telling observations/ visits also increased. The imporvement of students’ skills in telling observations/ student visits can be seen from the increasement in the average value of speech assessment indicated by students who do not perform activities that have been carried out, ie at pre cycle was 31.23% to 18.08% in the first cycle, 15% in the second cycle. Thus, it can be interpreted that the students’ skills in communicating observations /visits was increasing in each cycle.